Research techniques made simple: workflow for searching databases to reduce evidence selection bias in systematic reviews - Le Cleach, Laurence; Doney, Elizabeth; Katz, Kenneth A.; Williams, Hywel C.; Trinquart, Ludovic (Nature Publishing Group, 2016)
Clinical trials and basic science studies without statistically significant results are less likely to be published than studies with statistically significant results. Systematic reviews and meta-analyses that omit unpublished data are at high risk of distorted conclusions. Here, we describe methods to search beyond bibliographical databases to reduce evidence selection bias in systematic reviews. Unpublished studies may be identified by searching conference proceedings. Moreover, clinical trial registries—databases of planned and ongoing trials—and regulatory agency websites such as the European Medicine Agency (EMA) and the United States Food and Drug Administration (FDA) may provide summaries of efficacy and safety data. Primary and secondary outcomes are prespecified in trial registries, thus allowing the assessment of outcome reporting bias by comparison with the trial report. The sources of trial data and documents are still evolving, with ongoing initiatives promoting broader access to clinical study reports and individual patient data. There is currently no established methodology to ensure that the multiple sources of information are incorporated. Nonetheless, systematic reviews must adapt to these improvements and cover the new sources in their search strategies.